The ELEKTRONIK DISCHARGE PLANNING BERBASIS WHATSAPP CHATTING PEDULI UNTUK MENINGKATKAN ANGKA KUNJUNGAN KONTROL PADA PASIEN PASCA RAWAT INAP - Choirul Anam (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2024)
Number of control visits for post-inpatient patients at the AFM Arosbaya clinic from the last 3 months of data in 2023 is around 31.4%, concluded that the number of control visits is low. One of the causes the low number of control visits is poor implementation of discharge planning, this is proven by research 1 which found that 66% of respondents with good DP had control compliance. Paper-based DP has several weaknesses, including being easily lost, easily damaged and writing that is difficult to read. With the development of information, communication systems, it is necessary to develop WhatsApp-based electronic DP. This research method is a type of true experimental design with control research. Population in this study were post-inpatient patients at the AFM Arosbaya clinic in 2023, namely 701 patients. The sampling technique is purposive sampling, and the sampling technique is Accidental Sampling. The sample in the study was the average post-hospitalization patient at the AFM Arosbaya clinic in 2023 with an average number of 58 samples.The results of data analysis meet the requirements, where the P-Value Chi-Square value is significant (0.005), namely <0.05 or there is a relationship/correlation between the provision of WhatsApp-based e-DP and an increase in the number of control visits for post-hospitalization patients, but the correlation is weak with the contingency value 0.251. There were 20 patients who came for control before being given WhatsApp-based e-DP, while after being given WhatsApp-based e-DP there were 35 patients who came for control.Based on the research results above concluded that providing WhatsApp-based e-DP can increase the number of control visits post-hospitalization patients at the AFM Arosbaya clinic. The suggestion for this research is that further research needs to be carried out with a larger population,sample, a longer research time. Hopefully, future researchers can develop web-based discharge planning.